Perencanaan Prioritas Penanganan Jalan Provinsi Di Kecamatan Tampan Kota Pekanbaru Dengan Metode Analytical Hierarchy Process (AHP) - Liswi Arta Simorangkir; Mardani Sebayang; Yosi Alwinda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Based on the Work Plan and Budget Plan of Public Works Office, the Riau Province service in 2019, the provincial road handling program in Pekanbaru City, Riau Province is only based on the level of damage to road conditions and the level of road stability. The Ministry of Public Work has a definition of the purpose of road handling which is 100% stable roads. The level of road stability is determined by two criteria, the first one is steady in construction and the second is steady in traffic services. The purpose of this study is to obtain a priority sequence for handling provincial roads in the Tampan District of Pekanbaru appropriately by involving relevant parties. This study used the AHP method with 5 (five) criteria that were used to determine the priority of road handling, that is road conditions, traffic volume, accessibility, mobility and regional development. Based on AHP analysis, the importance level of each criterion is obtained to determine the priority of road handling. The results showed that the criteria for road conditions gains the highest weight 39.57% then level of accessibility 18.33%, then the criteria for regional development 18.25%, the criteria of traffic volume 12.51% and mobility criteria 11.35%. This study concludes that the most prioritized road sections in handling provincial roads in the Tampan District of Pekanbaru City in planning for 2020 is S.M Amin Road and Tuanku Tambusai Road and this study proves that the results of the author's analysis are different from the provincial roads planned by the government which to be handled in 2020, S.M Amin Road and Soekarno-Hatta Road. Keywords: Analytical Hierarchy Process, Handling Road, Priority Scale